Infection Dynamics of Severe Acute Respiratory Syndrome Coronavirus-2 Wild-type and Delta Variant of Concern in a Pediatric Cohort in Southern India - Asha Jyothi Penugonda; Deepayan Biswas; Murugan Thimiri Palani; Sangeetha Priya; Rajesh Kumar Subaschandrabose; Koshy Alan Valiaveetil; Belavendra Antonisamy; Rajeev Zachariah Kompithra; Leni Grace Mathew; Mahesh Moorthy (Current Medical Issues)
Background: Dynamics, severity, and immune response of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection vary between children and adults. There are only a few reports on the differential impact of variants in children, and none reported from low-and-middle-income countries. Materials and Methods: Between November 2020 and August 2021, we enrolled children under 16 years testing positive for SARS-CoV-2 by polymerase chain reaction (PCR). We compared virus characteristics (viral load, virus variant - Wild-type or Delta), disease severity (asymptomatic, mild-to-moderate, and severe), and immunity levels to the virus (anti-N and anti-S) after 4–6 weeks. Results: Of 79 children recruited, 29%, 59%, and 11% had asymptomatic, mild-to moderate, or severe presentations, respectively. Wild-type and delta variants presented with similar disease severity. For both variants, anti-S antibody levels were higher than anti-N antibody levels (P < 0.0001). Anti-S was also higher than anti-N among asymptomatic (P = 0.02) and mild-to-moderate disease (P < 0.0001). Children with higher virus loads had higher levels of both anti-S and anti-N antibodies (quartile [QS]1 versus QS3, P < 0.05). Among low (QS3) virus loads, wild-type anti-S levels were higher than delta infected (P = 0.003). In mild-to-moderate disease, the mean Ct value of wild type (32.5) was higher than that of delta infection (25.0) (P = 0.0083). Conclusions: In children, the antibody response is driven by viral load. In mild-to-moderate disease, higher loads of Delta variant of concern resulted in robust antibody response that was absent in severe disease. These results could inform potential responses to future SARS-CoV-2 variants and may guide decisions on targeted vaccination in children.